THE EFFECT OF CORPORATE GOVERNANCE ON EARNINGS MANAGEMENT - Hanna Wijaya; Denis Tifanny (Lembaga Riset dan Pengabdian Masyarakat (LRPM) Institut Bisnis Nusantara, 2020)
This study is conducted to examine the effects of corporate governance on earnings management. The variable used in this study includes accrual-based earnings management (proxied by discretionary accruals), real earnings management (proxied by abnormal cash flow from operations and abnormal overproduction) and corporate governance mechanism of audit committee expertise, audit committee size, managerial ownership, institutional ownership, and foreign ownership. Using purposive sampling method, this study uses a total of 318 firm-year observations of manufacturing companies listed in Indonesia Stock Exchange during the period 2015 – 2017. OLS multiple regression analysis through SPSS 19 is used to analyze the data for the purpose of hypothesis testing. The result of this study reveals that corporate governance mechanism especially, institutional ownership has a negative effect on accrual-based earnings management. On the other hand, corporate governance mechanisms, especially institutional ownership and foreign ownership has a negative effect on real earnings management.